Care for the Environment and Environmental Crime Based on Theravada Buddhist Philosophy - Tititampruk, Dittita; Ketsil, Tanet (International Journal of Criminology and Sociology, 2021)
From past to present, global compressions on human and environmental systems are more likely to increase than ever before in human history. With the science and technology advancement, we are living in the age of the global village that enables more convenient and brings us closer together. However, this also means that human being is suffering from global environmental crisis including the threat of war, economic crises, racial conflicts, environmental degradation, and environmental crime. This paper represents library-based work to date in Buddhist contemporary and useful perspectives and strategies on environmental protection and prevention in the backdrop of growing consumerism and capitalism influenced by western cultural in post-globalization era. Comparing to other countries, Thailand faces various environmental problems and some of them could become to environmental crime such as illegal wildlife trade; smuggling ozone-depleting substances; illicit trade in hazardous waste and pollution; illegal mining; illegal, unregulated and unreported fishing; illegal logging and associated trade in stolen timber. Since Thailand is one of largely Buddhist practical countries, measures to conserve the environment can draw on the principles and precepts of Lord Buddha’s teachings, known as Tripitaka. In Lord Buddha’s lifetime, environmental problems were not salient, but surprisingly, Lord Buddha recognised such problems because they are related to natural law. Accordingly, he established disciplinary rules for monks to live as models of not destroying the environment. The five precepts of Buddhism are the examples of the main principals in Buddhism which is regulations regarding the relation with environmental crime protection and humanity.